Equilibrium Contracts for Syndicates with Differential Information - Kobayashi, Takao (Econometrica, 1980)
This paper proposes a concept of the core for games with differential information, using Aumann’s notion of common knowledge. The concept is applied to solve the syndicate problem, for cases in which members have different private information on the uncertain prospects of each syndicate action and the contract (the risk sharing rule and the decision rule) is to be determined before they exchange their information.